U.S. environmental policy and politics a documentary history - Hillstrom, Kevin 1963- (Gale virtual reference library, 2010)
Explores the many ways throughout American history in which environmental concerns have intersected with issues of energy production and consumption, government regulation, private property rights, economic growth, and lifestyle choices.